(untitled) (diségno, 2022)
Given the continuing emergency due to the Covid-19 pandemic, the Workshop 3D Modeling & BIM was held on 7 April 2022 for the third consecutive time on a telematics platform; this limitation, however, allowed for a more significant number of participants. The seventh edition subtitled Information and 3D Modeling for the Cultural Heritage, in addition to maintaining its role as a privileged observatory on the use of Building Information Modeling (BIM) in architectural design, also explored the fields of investigation of surveying and visualization tools for the dissemination of the architectural built heritage and, more generally, of built heritage. [read more]